Morphology and molecular phylogeny reveal five new species of Hydnellum (Bankeraceae, Thelephorales) from China - Song, Chang-Ge; Sun, Yi-Fei; Wu, Dong-Mei; Gao, Neng; Liu, Shun; Xu, Tai-Min; Cui, Bao-Kai (Frontiers in Microbiology, 2022)
The genus Hydnellum is a kind of ectomycorrhizal fungi that can play a role in the material cycle by connecting the plant roots to the soil, and some species of Hydnellum are medicinal fungi with vital research value. The species diversity of Hydnellum is unclear in China. In this study, five new species of Hydnellum are described from China based on morphological characters and phylogenetic analyses inferred from two datasets of ITS+LSU and ITS+LSU+SSU+RPB2 sequences. H. chocolatum is characterized by its chocolate basidiomata with the fibrillose, spongy to tomentose pileal surface, and subglobose to globose basidiospores measuring (4.5–)5–6 × 4–5(–5.8) µm. H. concentricum is characterized by its zonate pileal surface, thin context, short stipe, presence of both simple septa and clamp connections in generative hyphae of spines, and subglobose to ellipsoidal basidiospores measuring (3.5–)4–5(–5.2) × (3.2–)3.5–5 µm. H. crassipileatum is characterized by its thick pileus with the reddish brown to greyish brown pileal surface, and subglobose to ellipsoidal basidiospores measuring 4–6(–6.5) × 4–5.5µm. H. melanocarpum is characterized by its vinaceous brown to black pileus with spongy pileal surface, presence of both simple septa and clamp connections in generative hyphae of spines, and subglobose basidiospores measuring 4.5–5.5(–6) × (3.5–)3.8–5.1µm. H. radiatum is characterized by its radially aligned stripes on pileal surface, greyish brown context, short stipe, and subglobose to ellipsoidal basidiospores measuring (3.5–)4–5 × 3–4.5(–5) µm. Full descriptions, illustrations, and phylogenetic tree to show the placement of the new species are provided.